PERENCANAAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM MENGOPTIMALKAN PENGELOLAAN ZAKAT DI KABUPATEN PINRANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The result of the study shows that there are forms of planning for the National Amil Zakat Agency (BAZNAS) in zakat management in Pinrang Regency, namely, global plans, strategic plans, and operational plans. Efforts to optimize the management and distribution of zakat at the National Amil Zakat Agency (BAZNAS) of Pinrang Regency are carried out in two ways, namely through UPZ and utilizing distribution through UPZ and utilizing distribution through moments such as mauled, Nuzulul Qur’an and other activities. And sometimes out of distribution planning when there are important things such as natural disasters so the National Amil Zakat Agency (BAZNAS) has to leave the planning.